Mykhailo Ivanovych Sytenko (to the 135th anniversary of his birth) - Golubeva, Inna; Shevchenko, Olena; Tankut, Volodymyr; Dynnik, Olexii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is dedicated to the 135th anniversary of the birth of prof. MI Sitenko. November 2020 marked the 135th anniversary of the birth of the outstanding orthopedic traumatologist and health care organizer, corresponding member of the Academy of Sciences of the Ukrainian SSR, Professor Mykhailo Ivanovych Sytenko. The merits of Professor MI Sytenko are difficult to overestimate. His name is associated with the formation and development of orthopedics, traumatology, prosthetics and rehabilitation care in our country. With his assistance, a wide state network of institutions was created, which provided the population with highly qualified orthopedic-traumatological and prosthetic-orthopedic care, and carried out rehabilitation measures.